Telaah Maqashid Syariah Atas Efektivitas Penyelesaian Perkara Penundaan Kewajiban Pembayaran Utang (PKPU) Perbankan Syariah di Kota Medan - Wulan Dayu; Muhammad Syukri Albani (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
In the business world, the chance of a loss is almost proportional to the possibility of making a profit. One of the impacts of losses in a business is the financial difficulties experienced by business actors which lead to the inability to repay all of their obligations to their business partners, including debt repayment obligations in terms of capital from banks. This study aims to explain the legal basis in the settlement of Islamic bankruptcy in the Commercial Court in the decision No.01/Pdt-Sus-PKPU/2015/PN Niaga Mdn, in addition to explaining whether in the decision No.01/Pdt-Sus-PKPU/2015/PN Niaga Mdn is following maqashid sharia based on Islamic law. The research method used is a qualitative research method, with the nature of field research (field research). The research approach used in the compilation of this study uses normatively. Data collection techniques used to collect research data are using a survey, in depth interview with Mr. Jamaluddin, SH, MH, and all MUI Medan commissariat and integrated the documentation method by collecting documents related to Islamic banking verdicts which are decided in the Medan District Court and other supporting documents. The results of this study are that in the decision No.01/Pdt-Sus-PKPU/2015/PN Niaga Mdn following sharia maqashid by referring to the compatibility of the source between the positive legal basis with the principles of Islamic economics.